Development of an introduction to basic mathematics textbook based on contextual teaching and learning integrated with Islamic values - Erita, Selvia; Oktafia, Mesi (Universitas Islam Negeri Raden Intan Lampung, 2025)
There is no introduction to an introductory mathematics textbook that integrates Islamic values through contextual teaching and learning. Therefore, this study aims to fill this gap by developing a textbook that meets the required standards. To achieve this objective, research and development (R and D) were conducted using the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used included expert validation, student response, and lecturer response questionnaires. Furthermore, the data were analyzed both qualitatively and quantitatively. The results showed that the textbook fulfilled the specified quality standards and improved students' ability to produce relevant teaching materials tailored to their needs. Specifically, the results from material, design, and Islamic experts showed percentages of 85.49%, 85.25%, and 88.02%, respectively, falling into the highly valid category. In the small group trial, the student practicality questionnaire produced 83.30%, while 86.85% was obtained for the lecturer practicality questionnaire. In conclusion, the Introduction to Basic Mathematics textbook, which was based on contextual teaching and learning, integrated with Islamic values, was both valid and practical. This finding has implications for developing teaching materials by integrating Islamic values in Islamic higher education.